Planning Design A Website-Based Mechanic Information System In Bangkinang Kota - Imam Azizan; Novi Yona Sidratul Munti; Hanantatur Adeswastoto (Journal of Engineering Science and Technology Management, 2022)
The existence of information systems in various fields of companies and other industries, making a company / industry becomes developed. Menuru (Gama, 2011), the importance of information systems provides a function of presenting information, conveying information that can be processed and accessed easily. So with the development of information technology and information systems are able to make everyone to create new businesses that can increase the income of a region in particular and the income of the country in general. The application of information systems in automotive is important because it will be very supportive in processing data, transactions, and making reports easily computerized. To increase the number of existing workshop customers, the service or support of the information system is very important to maintain the continuity of the workshop, especially to increase the amount of revenue through increasing the number of customers. Such as service facilities that come to where vehicle users are located to provide ease of use of service facilities through the creation of web-based applications.